The Relationship Between Chinese EFL Learners’ Resilience and Academic Motivation - Zhang, Bo (Frontiers in Psychology, 2022)
With the recent adoption of Positive Psychology in foreign language education, academic motivation and resilience as secondary components of positive psychology have started to receive academic attention. Undoubtedly, students require constant motivation because learning a foreign language is a long-term effort especially in the first stage that they usually lose their interest and motivation. When students are academically motivated, they can put high effort to learn the language. This study aims to inspect the relationship between Chinese EFL learners’ resilience and academic motivation. To this end, 482 students from different colleges and universities in China were selected and they completed the resilience and academic motivation questionnaires. Spearman’s rho index and multiple regressions were run for data analyses. Results of the study indicated that there is a positive and significant association showing a relationship between these two constructs. Moreover, two components of motivation, namely interjected regulation and external regulation by attendance proved to be the best predictors of learners’ resilience. The paper concludes with some pedagogical implications; for instance, motivation can be considered as a primary point for the progress of resilience for the next steps of language success.